2001
DOI: 10.1023/a:1012227302373
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A collection of nitrile-hydrolysing rhodococci was isolated from sediments sampled from a range of deep coastal, and abyssal and hadal trench sites in the NW Pacific Ocean, as part of our programme on the diversity of marine actinomycetes. Nitrile-hydrolysing strains were obtained by batch enrichments on nitrile substrates with or without dispersion and differential centrifugation pre-treatment of sediments, and were recovered from all of the depths sampled (approximately 1100-6500 m). Two isolates obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…It was supported by the formation of acetic acid, acetamide and ammonia during the biotransformation process as previously also reported by Asano et al (1982) and Kim et al (2001). Basically, the activity of nitrile compounds biotransformation characterized by the formation of ammonia (Heald et al 2001). Kobayashi et al (1992) reported that the amino acid sequences of the two sub-units are not interconnected and the structural genes of NHase are usually adjacent in the same operon, although the coding sequence of sub-units of α and β are variable.…”
Section: Hastuty Et Alsupporting
confidence: 63%
See 1 more Smart Citation
“…It was supported by the formation of acetic acid, acetamide and ammonia during the biotransformation process as previously also reported by Asano et al (1982) and Kim et al (2001). Basically, the activity of nitrile compounds biotransformation characterized by the formation of ammonia (Heald et al 2001). Kobayashi et al (1992) reported that the amino acid sequences of the two sub-units are not interconnected and the structural genes of NHase are usually adjacent in the same operon, although the coding sequence of sub-units of α and β are variable.…”
Section: Hastuty Et Alsupporting
confidence: 63%
“…Until now, the majority of bacteria producing NHase and amidase enzymes have been reported from shallow marine sediment (Langdahl et al 1996), deepsea sediments (Heald et al 2001), geothermal habitats (Pereira et al 1998), and various soils (Blakey et al 1995;Brandão et al 2003). Polluted environment (Cahill 2004;Kabaivanova et al 2005;Coffey et al 2009) have also been explored in the discovery of novel bacteria producing NHase and amidase enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction, consisting of the nitrile (at final concentrations of 20 mM) and 20 mg (wet weight) of resting cells in 10 mL phosphate buffer (pH 6.5, 100 mM), was carried out at 30°C and 168 rpm. Samples (100 μL each) from the reaction mixture were taken at regular intervals, and cells were removed by centrifugation (21, 37, 38). The amount of the produce ammonia was measured as described above and an analytical method was done as follows.…”
Section: Methodsmentioning
confidence: 99%
“…The flow of helium was maintained at 30 mL.min -1 . Five μL of the reaction mixture was injected and the residual substrate concentration was calculated against the standard curve (32, 38, 39). …”
Section: Methodsmentioning
confidence: 99%
“…There are reports indicating elevated levels of amidase enzyme in soil samples [3]. Amidases which form an integral component of nitrile converting biocatalysts usually operate at narrow pH (neutral or slightly alkaline) and temperatures which makes it a difficult choice for industrial biocatalysis [15,24]. In such conditions immobilization of microbial cells offers several advantages like tolerance to toxic substances reusability of the biocatalysts and continuous operation [26].…”
Section: Introductionmentioning
confidence: 99%